INTERPRETATION OF MAGNETIC FIELD INTENSITY OVER REGION OF MANGANESE ORE DEPOSIT AT BAKIN-RUWA AND DARANNA COMMUNITY, KEBBI STATE NORTHWEST NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Aeromagnetic data that covers part of Northwestern Nigeria was processed and qualitatively interpreted with the aim of determining the magnetic field intensity associated with regions where manganese ore deposits are exposed. The study was undertaken to determine the possible continuity of the deposits beyond the current exposures.  The characteristics and continuity of associated magnetic field intensity beyond the locations where used for this purpose.  To achieve the above, four quarter degree sheets of high-resolution aeromagnetic data that covers the region was acquired and processed. The acquired data were combined into a composite data and then upward continued. Regional residual separation of the upward continued data was used to produce magnetic field intensity map of the area. The variations in the magnetic field intensity around the area was attributed to different geological units around the area and region where manganese ore deposits are located. The location of manganese ore deposits was found to correspond to part and edge of region which shows high magnetic field intensity. This region extends beyond the known exposures of manganese ore deposits hence suggest possible continuation of the deposits beyond the area
Keywords: Manganese, magnetic-field, susceptibility, regional, residual, intensity